The East Kainji languages of Central Nigeria (Afrika und Übersee, 2020)
The paper is an overview of current scholarship on the East Kainji language group of Central Nigeria. It reviews the existing published and manuscript sources and describes recent research, as well as the development of orthographies for some languages. Many East Kainji languages are severely threatened and some have gone extinct within the period under review. The paper presents an internal classification of the group and briefly discusses the external relationships of these languages. On the basis of existing data, a review of the basic phonology and noun class prefix systems is given.
Keywords: East Kainji languages; classification; status; Nigeria